The exchange of words speech, testimony, and intersubjectivity - Moran, Richard 1953- (New York Oxford University Press, 2018)
The capacity to speak is not only the ability to pronounce words, but the socially-recognized capacity to make one's words count in various ways. We rely on this capacity whenever we tell another person something and expect to be believed, and what we learn from others in this way is the basis for most of what we take ourselves to know about the world.

In The Exchange of Words, Richard Moran provides a philosophical exploration of human testimony as a form of intersubjective understanding in which speakers communicate by making themselves accountable for the truth of what they say. The book brings together themes from literature, philosophy of language, moral psychology, action theory, and epistemology, for a new approach to this fundamental human phenomenon.

The account developed here starts from the difference between what may be revealed in one's speech (like a regional accent) and what we explicitly claim and make ourselves answerable for. Some prominent themes include: the meaning of sincerity in speech, the nature of mutuality and how it differs from 'mind-reading', the interplay between the first-person and the second-person perspectives in conversation, and the nature of the speech act of telling and related illocutions as developed by philosophers such as J. L. Austin and Paul Grice.
Everyday dialogue is the locus of a kind of intersubjective understanding that is distinctive of the transmission of reasons in human testimony, and The Exchange of Words is an original and integrated account of this basic way of being informative to and in touch with one another.
Preface -- Acknowledgments -- Chapter One: Speech, Intersubjectivity, and Social Acts -- Chapter Two: Getting Told and Being Believed -- Chapter Three: Sincerity and Self-Expression -- Chapter Four: The Claim and the Encounter -- Chapter Five: Illocution and Interlocution -- Chapter Six: The Social Act and its Self-Consciousness -- Chapter Seven: The Self and its Society -- Bibliography
Includes bibliographical references (pages 221-227) and indexes.
Keywords: Intersubjectivity; Social epistemology; Speech acts (Linguistics).; Testimony (Theory of knowledge).